The Problem of the Narrative Impossibility in Clarice Lispector and Primo Levi - Afonso, Elaine [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2017)
This article aims at working with the problem of the narrative impossibility. This matter can be noticed in two authors, namely, Clarice Lispector and Primo Levi. However, this impossibility to narrate is noticed in different and particular ways in these authors. Clarice wants to capture the moment and fix it, but she notices that it is not possible to capture this moment without betraying it. On the other hand, Levi tries to reconstitute, through language, a traumatic event and is aware of the impossibility to recount all the facts completely. The result of this impossible recount is the fragmentation, which marks the writing of both authors, and this is considered the hell of their works.
Keywords: Clarice Lispector; Fragmentation; Narrative Impossibility; Primo Levi; Writing